A survey of patients with surgical wounds healing by secondary intention; an assessment of prevalence, aetiology, duration and management. Issue 2 (May 2017) - Chetter, I.C.; Oswald, A.V.; Fletcher, M.; Dumville, J.C.; Cullum, N.A.
Abstract: Background: Surgical wounds healing by secondary intention (SWHSI) are often difficult and costly to treat. There is a dearth of clinical and research information regarding SWHSI. The aim of this survey was to estimate the prevalence of SWHSI and to characterise the aetiology, duration and management of these wounds. Methods: Anonymised data were collected from patients with SWHSI receiving treatment in primary, secondary and community settings. Over a two weeks period, data were collected on the patients, their SWHSI, clinical and treatment details. Results: Data were collected from 187 patients with a median age of 58.0 (95% CI = 55 to 61) years. The prevalence of SWHSI was 0.41 (95% CI = 0.35 to 0.47) per 1000 population. More patients with SWHSI were being treated in community (109/187, 58.3%) than in secondary (56/187, 29.9%) care settings. Most patients (164/187, 87.7%) had one SWHSI and the median duration of wounds was 28.0 (95% CI = 21 to 35) days. The most common surgical specialities associated with SWHSI were colorectal (80/187, 42.8%), plastics (24/187, 12.8%) and vascular (22/187, 11.8%) surgery. Nearly half of SWHSI were planned to heal by secondary intention (90/187, 48.1%) and 77/187 (41.2%) were wounds that had dehisced. Dressings were the most common single treatment for SWHSI, received by 169/181 (93.4%) patients. Eleven (6.1%) patients were receiving negative pressure wound therapy. Conclusions: This survey provides a previously unknown insight into the occurrence, duration, treatment and types of surgery that lead to SWHSI. This information will be of value to patients, health care providers and researchers. Highlights: Surgical wounds healing by secondary intention (SWHSI) are a common problem with a prevalence of 0.41 per 1000 population. Approximately 50% of SWHSI are planned. The surgical specialities most commonly associated with SWHSI were colorectal, plastics and vascular surgery. The median duration of SWHSI at the time of the survey was 28.0 (95% CI = 21 to 35) days. Negative pressure wound therapy was used in 6.1% of SWHSI at the time of this survey.